Phase 2 study of preoperative radiation with concurrent capecitabine, oxaliplatin, and bevacizumab followed by surgery and postoperative 5‐fluorouracil, leucovorin, oxaliplatin (FOLFOX), and bevacizumab in patients with locally advanced rectal cancer: ECOG 32041. Issue 8 (3rd January 2013) - Landry, Jerome C.; Feng, Yang; Cohen, Steven J.; Staley, Charles A.; Whittington, Richard; Sigurdson, Elin Ruth; Nimeiri, Halla; Verma, Udit; Prabhu, Roshan S.; Benson, Al Bowen
Abstract: BACKGROUND: Recent studies have demonstrated the feasibility of combining oxaliplatin with 5‐fluorouracil (5‐FU) or capecitibine and radiation therapy. The addition of bevacizumab to chemotherapy improves overall survival for metastatic disease. We initiated a phase 2 trial to evaluate preoperative capecitabine, oxaliplatin, and bevacizumab with radiation therapy followed by surgery and postoperative 5‐FU, leucovorin, oxaliplatin (FOLFOX) and bevacizumab for locally advanced rectal cancer. METHODS: Fifty‐seven patients with resectable T3/T4 rectal adenocarcinoma were enrolled. Preoperative treatment was capecitabine (825 mg/m 2 twice daily from Monday to Friday), oxaliplatin (50 mg/m 2 weekly), bevacizumab (5 mg/kg on days 1, 15, 29), and radiation therapy (50.4 Gy). Surgery was performed by 6 weeks after neoadjuvant therapy. Beginning 8 to 12 weeks after surgery, patients received FOLFOX plus bevacizumab (5 mg/kg) every 2 weeks for 12 cycles. RESULTS: Fifty‐four of 57 enrolled patients were eligible. Forty‐nine (91%) patients completed preoperative therapy and underwent surgery. Nine patients (17%; 90% confidence interval, 9%‐27%) achieved pathologic complete response. Thirty‐two patients (59%) experienced pathologic tumor downstaging, and 53% and 15% of patients experienced worst grade 3 and grade 4 acute toxicity, respectively. Forty‐seven percent of patients who underwent surgery experienced a surgical complication. CONCLUSIONS: The primary endpoint of a 30% pathologic complete response rate was not reached; however, the majority of patients experienced pathologic downstaging with this regimen. Increased wound‐healing delays and complications may have been related to the addition of bevacizumab, oxaliplatin, or both. Continued observation of these patients will establish the long‐term morbidity and efficacy of this combined modality approach. Cancer 2013. © 2012 American Cancer Society. Abstract : The addition of oxaliplatin and bevacizumab to fluoropyrimidine‐based neoadjuvant chemoradiation for locally advanced rectal cancer resulted in pathologic tumor downstaging in the majority of patients, with a pathologic complete response rate of 17%. Increased wound healing delays and complications may have been related to the addition of bevacizumab, oxaliplatin, or both.